Penelitian pengaruh penambahan karet reclaim terhadap sifat- sifat kuat tarik, kemuluran dan volume terkikis kompon karet - Prayitno Prayitno (Majalah Kulit, Karet, dan Plastik, 1990)
Reprocessed of wastevulcanized rubber products, known as reclaim rubber, is used as a filler in rubber soles. Uncorrect usage of reclaim rubber in rubber sole manufacturing can decrease the product performance such as as tensile streangth, elongation break and abrasion resistance.       In this experiment, by comparison of 30, 40, 50, 60 and 70 parts of reclaim rubber to the 100 part of natural rubber (RSS) sow that tensile strength decreased to 174.138, 160.118, 140.574, 134.092, and 449,60, 437.20, 426.00, 403.80 and 396.60% nrespectively, whereas abrasion resistance decreased to 0,2491, 0,4781, 0,5267, 0.7909, and mm3 / kgm respectively.